Juridical Analysis of the Legal Relationship Between Doctors and Patients in Health Services - Enny Agustina (Universitas Kuningan, 2020)
The doctor and patient relationship is a pattern that is born among the doctor and the patient before continuing to the act of health care. And health services, is a concept used in providing health services to the community. Health services is a sub-system of health services whose main purpose is health services in terms of Preventive (preventive), Promotive (improving health,) Curative (healing health) and Rehabilitative (recovery) are all efforts mobilized by the government in improving the quality of health services prime and in accordance with standard operating procedures and health service standards. This study uses a method of approach to the community so that the public knows in more detail about the juridical analysis of the legal relationship among doctors and patients in health services. The results of this study are in terms of the legal aspects of health, the relationship among doctors and patients cannot decide what is called health services by doctors who have a direct role in improving tasks for the community in order to realize a good and quality society. Analisis Yuridis Hubungan Hukum Antara Dokter Dan Pasien Dalam Layanan Kesehatan Hubungan dokter dan pasien merupakan pola yang lahir antara dokter dan pasien sebelum berlanjut pada tindakan pelayanan kesehatan. Dan pelayanan kesehatan,merupakan sebuah konsep yang digunakan dalam memberikan layanan kesehatan kepada masyarakat. Pelayanan kesehatan adalah sebuah sub sistem pelayanan kesehatan yang ditujuan utamanya adalah pelayanan kesehatan dalam hal Preventif (pencegahan), Promotif (peningkatan kesehatan,) Kuratif (penyembuhan kesehatan) dan Rehabilitatif (pemulihan) merupakan segala upaya yang dikerahkan oleh pemerintah dalam peningkatan mutu pelayanan kesehatan yang prima dan sesuai dengan standar prosedur dan standar operasional prosedur pelayanan kesehatan. Penelitian ini menggunakan metode pendekatan kepada masyarakat sehingga masyarakat tahu lebih detail tentang analisis yuridis hubungan hukum antara dokter dan pasien dalam peyanan kesehatan. Hasil penelitian ini yaitu Dalam hal aspek hukum kesehatan, hubungan antara dokter dan pasien tidak dapat memutuskan apa yang disebut layanan kesehatan oleh dokter yang memiliki peran langsung dalam tugas-tugas perbaikan untuk masyarakat dalam rangka mewujudkan masyarakat yang baik dan berkualitas.